Wireless Broadband Opportunities through TVWS for Networking in Rural areas of Africa - Dramane Ouattara; Mohamed Aymen Chalouf; Francine Krief; Omessaad Hamdi (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2015)
In this paper, we propose a new approach based on Cognitive Radio technology to address the challenges for ensuring connectivity in remote areas of Africa. Indeed, the current network coverage is concentrated around the cities with high density of population. Through the deployment of Cognitive Radio, emergency services in rural areas will benefit from low cost access networks. Cognitive Radio will be used to manage the selection/switching across different frequency UHF/VHF bands or TV White Spaces (TVWS), while avoiding interference.